Lichenoid eruptions in children - Wiśnicka, Beata; Reich, Adam; Baran, Eugeniusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2005)
Lichenoid eruptions, of which lichen planus is the prototype, are considered to be a long list of diseases, where shiny, flat-topped, polygonal papules of different sizes are present. In most cases the etiology of the disease is not known, but immunologic component seems to be quite important in some instances. Many of them more often affect children, like lichen nitidus, lichen striatus, lichen spinulosus, Gianotti-Crosti syndrom or frictional lichenoid eruption; others are more frequent in the adult population. In some cases biopsy is required to establish a proper diagnosis. In this review we would like to present lichenoid eruptions in children, which are quite often only remotely related disorders.